Pembuatan Komposit Bioplastik Konduktif Berbasis Tepung Tapioka Dengan Penambahan Electrochemichal And Mechanical Liquid Exfoliation Graphene - Heri Rahmana; Amun Amri; Syelvia Putri Utami (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Conductive bioplastics are biodegradable plastics that have a good ability to conduct electrical current. This study aims to create a conductive tapioca-based bioplastic composite with the addition of EMLE graphene (Electrochemical and Mechanical Liquid Exfoliation) and study the effect of the amount of EMLE graphene addition to the tensile strength and transparency of bioplastics. Conductive bioplastic production was held by using solution intercalation method. The main raw material was tapioca flour as matrix and graphene as filler. Graphene can be produced by using the Electrochemical and Mechanical Liquid Exfoliation method which made in the liquid phase and mechanically crushed or mashed by using a blender. The products were analyzed by using conductive bioplastic tensile test and transparency. The best tensile test value was 3.92 Mpa with elongation 8.516% in addition for 9% graphene and 30 minutes. The best transparency value was obtained 88.31% without graphene addition.Keywords: bioplastics, EMLE, graphene, solution intercalation, tapioca flour.